Perbandingan Minat dan Hasil Belajar Siswa yang Dibelajarkan dengan Model Pembelajaran Inkuiri Terbimbing dengan Inkuiri Terstruktur pada Mata Pelajaran Biologi - Karim, Hilda; Lodang, Hamka; Nurhadi, Muhammad (Universitas Negeri Makassar, 2021)
Abstract. The research aims to know 1) to know of learning interest and student learning outcome with learned by guided inquiry and learned by structured inquiry on biology lesson, 2) to know of comparison learning interest and student learning outcome with learned by guided inquiry and learned by structured inquiry on biology lesson. The subjects of research are all classXIMIAMIA seniorhigh school number 2 Palopo that consisted of five class, whilethe sample used consist oftwo class and taken randomly. Design of research used RandomizedPretestPosttest Comparison Group Design. The data of learning interest is obtained with questionnaire while learning outcome with learning test results. The collected data is analyzedby descriptive used NGain and inferential statistic used Independent Sample t Test with significance level Î± = 0.05. The results of descriptive statistic showed learning interest in lowcategory with value of NGain 0.18 and 0.16 while learning outcome in medium category withvalue 0.51 and 0.38. The results of hypotheses test showed two groups was different significantly with value of learning interest and learning outcome is 0.000 and 0.021,so it wasconclude that there was difference in learning interest and student learning outcome with learning by guided inquiry and learning by structured inquiry on biology lesson. Keywords: guided inquiry,structured inquiry, learning interest, learning outcome.